The Global Securitized Subprime Market Crisis - O'Hara, Phillip (Sage Publications, 2009)
This paper examines the global securitised subprime crisis through the lens of core general principles of political economy. The principle of historical specificity is used to situate the crisis in cycles and historical time. The principle of circular and cumulative causation scrutinises the role of multiple factors and how they cumulatively impact on the system. The principle of contradiction explores the relationship between finance and industry through deregulation and changing industrial leadership at the global level. The principles of financial innovation and heterogeneous agents link to the intricacies of the different roles of economic agents in the circuit of mortgages and securitisation. And finally the principle of risk and uncertainty examines the contradictory role of complex institutions and calculative models of risk in the generation of high systemic uncertainty during booms in the cycle.